Efecto de la aplicación de cuatro dosis del biofertilizante fertibacter en el rendimiento del cultivo de maíz (zea mays l.) en la zona de Babahoyo, provincia de Los Ríos - Valencia Tigrero, Ignacio Rodolfo (2013)
This research was carried out on the grounds of the Faculty of agricultural sciences, Universidad technique of Babahoyo; located in the 7.5 Km of the via Babahoyo - Montalvo, province of Los Ríos, in maize hybrid 'Triumph NB'-7253 and '30F35', in the presence of four doses of fertilizer Fertibacter - corn, 0 – 200 - 300 - 400 y 500 g/ha; with the purpose of((: a) evaluate the agronomic performance of hybrid maize in the presence of the biofertilizer Fertibacter; b) identify the most appropriate dose of the biofertilizer Fertibacter to maximize the performance of grain; and (c) analyze economically the grain yield based on the cost of treatments. The experimental design was used "Complete random blocks" in accordance with factorial 2 x 5 giving a total of 10 treatments, 3 repetitions. The experimental plot consisted of 4 rows of 6 m long distanced to 0.70 m, giving an area of 16.8 m2; While the useful area was determined by the 2 Central rows, giving an area of 8.4 m2. The distance between plants in each row was 0.20 m; with a population density of 71.428 plants per hectare.